(untitled) - Chissick, Michael (London, 2002)
Electronic Commerce: Law and Practice provides a clear, practical approach including case studies illustrating legal pitfalls and opportunities, and a detailed transactional analysis on how to set about trading on-line. Since the last edition there has been much activity in electronic commerce by way of UK, European and US legislative developments and general interest in the area has been growing due to increased use of the Internet for commercial transactions and the burgeoning number of Internet start-up companies. This new edition of an acclaimed work brings you completely up-to-date with every aspect of the law relevant to the use of electronic sales channels, one of the fastest growing areas of commerce.
Keywords: Electronic commerce,Business law,Thương mại điện tử; Law and legislation,Pháp chế và luật pháp; Great Britain,Great Britain,Vương quốc Anh